1999
DOI: 10.1038/sj.gene.6363630
|View full text |Cite
|
Sign up to set email alerts
|

An IL-13 promoter polymorphism associated with increased risk of allergic asthma

Abstract: IL-13 plays a crucial role in the development of allergic asthma by several mechanisms, including induction of IgE antibodies, airway eosinophilia and hyper-reactivity. We previously established a deregulated production of IL-13 by T cells from allergic asthma patients. In this report we describe the identification of a novel IL-13 promoter polymorphism (C to T exchange) at position −1055. The IL-13 −1055 TT genotype is associated with allergic asthma (P = 0.002), altered regulation of IL-13 production (P Ͻ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
171
5
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(185 citation statements)
references
References 34 publications
6
171
5
2
Order By: Relevance
“…The T allele at position À1111 results in increased binding of the NFAT protein to this region. 46 These studies suggest that the À1111T4C SNP is functionally important and could account for the observed association of the À1111T allele and asthma-related phenotypes. Alternatively, the statistical association of the À1111T allele with asthma and related phenotypes could be due to LD with a different causative mutation.…”
Section: Patterns Of Genetic Diversity At Il13mentioning
confidence: 92%
See 1 more Smart Citation
“…The T allele at position À1111 results in increased binding of the NFAT protein to this region. 46 These studies suggest that the À1111T4C SNP is functionally important and could account for the observed association of the À1111T allele and asthma-related phenotypes. Alternatively, the statistical association of the À1111T allele with asthma and related phenotypes could be due to LD with a different causative mutation.…”
Section: Patterns Of Genetic Diversity At Il13mentioning
confidence: 92%
“…The common À1111T allele in the promoter region has also been associated with asthma, high levels of serum IL-13 and IgE, as well as asthma-proximal phenotypes (bronchial hyper-responsiveness and skin-test responsiveness) in case-control studies with European populations. 46,8 The À1111T4C SNP is located in a region containing a binding site of the nuclear factor of activated T cells (NFAT) transcription factor that regulates IL13 and IL4 gene expression. The T allele at position À1111 results in increased binding of the NFAT protein to this region.…”
Section: Patterns Of Genetic Diversity At Il13mentioning
confidence: 99%
“…9 More recently, this polymorphism was found to be associated with elevated antibody levels against malaria antigens in the Fulani of West Africa. 10 An IL-13 promoter polymorphism, IL-13 À1055C4T, is known to affect the expression level and to be associated with allergic asthma 11 and chronic obstructive pulmonary disease. 12 These observations raise the question of whether the IL-3 À16T4C, IL-4 À590C4T, and IL-13 À1055C4T polymorphisms are associated with severity of malaria.…”
Section: Introductionmentioning
confidence: 99%
“…The C to T change at À1055 of IL-13 has been suggested to alter IL-13 production through the binding of NF-AT to the IL-13 promoter. 11 Although the role of IL-13 in the host defense or the pathogenesis of severe malaria has not been established yet, increased production of IL-13 may prevent the onset of severe malaria. The biological significance of IL-13 in malaria patients should be clarified in future studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in the Netherlands, subjects with the TT genotype of SNP rs1800925 exhibited significantly weaker relative inhibition of IL-13 production upon additional stimulation with anti-CD2 compared to those with the CC or CT genotype [22]. Cameron and colleagues have shown that the T allele of SNP rs1800925 enhanced IL13 promoter activity in primary human and murine CD4 + Th2 lymphocytes through Yin-Yang 1-dependent attenuation of STAT6-mediated promoter repression and that mitogen-activated peripheral blood mononuclear cells from pregnant women with the TT genotype of SNP rs1800925 secreted significantly higher levels of IL-13 compared with those from pregnant women with the CC or CT genotype [23].…”
Section: Discussionmentioning
confidence: 99%